Analysis and Design of a High-Coupling-Factor Marchand-Balun Variant Suitable for Standard Silicon IC Process and Its Wide-Band Gilbert Mixer Application - Chinchun Meng; Sheng-Che Tseng; Tsung-Mao Chao; Kuan-Chang Tsung (IEEE Access)
In this paper, a planar Marchand balun and its modification version are analyzed and designed on the standard lossy silicon substrate of $10~Ω $ -cm resistivity. The analysis shows that both Marchand balun’s outputs are always equal in magnitude and opposite in phase within all frequency ranges even on a lossy silicon substrate. The high-coupling-factor modified Marchand balun has a much wider operation bandwidth than the prototype. Additionally, the multi-layer-metal stacking capability in silicon IC technology favors implementing the coupled line with a high coupling factor. Two Marchand baluns are formed by two back-to-back $λ $ /4 coupled lines. The modified one has the duality topology to the original Marchand balun in structure but with a higher coupling factor when both Marchand baluns are designed with the same characteristic impedance, the geometric mean impedance of the even-/odd-mode characteristic impedances, of the constituent coupled lines. These two types of Marchand baluns are implemented on a standard silicon substrate, and obviously the modified Marchand balun has a better performance with outputs of $180± 6^{° }$ phase difference and ±0.5 dB magnitude imbalance from 4 GHz to 27 GHz. The maximum transmission coefficient is approximately −6 dB, and the 3-dB fractional bandwidth is 148%. Finally, two wideband Marchand balun applications in a Gilbert micromixer are demonstrated using 0.35- $μ $ m SiGe BiCMOS technology. The modified Marchand balun integrated at the LO stage of the mixer offers more than 30% operation bandwidth than the conventional Marchand balun does.